Accuracy verification in ultrasonic elasticity measurement within intima-media complex visible range using phantom experimental system. (7th April 2021) - Akiyama, Seira; Mori, Shohei; Arakawa, Mototaka; Kanai, Hiroshi
Abstract: Studies to investigate the ultrasound elasticity measurement of the carotid artery, for early detection of arteriosclerosis, are ongoing. In the long-axis cross-sectional measurement in vivo, the position where the intima-media complex (IMC) is visible on the B-mode image was assumed to be the central axis of the short-axis view of the carotid artery. However, the IMC is also visible near the central axis of the short-axis view of the carotid artery. In the present study, accuracy in elasticity measurement within the IMC visible range was evaluated through a phantom experiment. The elasticities of the posterior wall measured at plural points within the IMC visible range differed by up to 6%. From the experimental results, we concluded that for the highest accuracy, it is important to measure along the central axis of the short-axis view of the carotid artery.